Design of buffer property for the new enrichment method of circulating tumor cell based on immunomagnetic-negative separation - Kazuaki Hoshi; Yasinjan Hashim; Shinsaku Togo; Shoko Saiwaki; Hiroaki Motomura; Issei Sumiyoshi; Shun Nakazawa; Yusuke Ochi; Chieko Miyoshi; Rihyang Heo; Yoko Tabe; Kanae Abe; et al. (Computational and Structural Biotechnology Journal)
Metastasis is a significant contributor to cancer-related mortality and a critical issue in cancer. Monitoring the changes in circulating tumor cells (CTCs) with metastatic potential is a valuable prognostic and predictive biomarker. CTCs are a rare population in the peripheral blood of patients with cancer. The enrichment process is extremely important for the isolation of clinically significant CTC subpopulations, which can then be used for further analysis. The present study postulates that the buffer serves as an essential field for immunomagnetic separation, thereby enhancing the efficacy of CTC enrichment in peripheral blood. This, in turn, facilitates CTC detection. Here, we describe the design of buffers for developing a novel immunomagnetic-negative separation method for CTC enrichment. During the design process, the buffer properties of the floating and cell coatings had a synergistic effect on the efficiency of cell enrichment in blood samples. The efficacy of the method was evaluated using peripheral blood samples from patients with non-small cell lung cancer (NSCLC) and small cell lung cancer (SCLC). The developed method enriched clinically relevant CTC subpopulations that expressed the epithelial-mesenchymal transition (EMT)-related molecule vimentin and/or the cancer immune checkpoint marker programmed death ligand 1 (PD-L1). Furthermore, it was applicable as a part of the enrichment process in a TelomeScan® (OBP-401)-based CTC detection assay with high sensitivity and specificity. From the perspective of methodological approaches, the design of buffer properties can be useful for developing a highly versatile enrichment method for handling CTC heterogeneity.